2011
DOI: 10.1542/peds.2011-1049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Night-Team System on Resident Sleep and Work Hours

Abstract: Implementation of a night-team system was unexpectedly associated with decreased sleep hours. As residency programs create work schedules that are compliant with the 2011 Accreditation Council for Graduate Medical Education duty-hour standards, resident sleep should be monitored carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…29,30,[33][34][35][36]41,43,46 A minority of studies found a favorable impact on resident well-being (4 of 17, 24%; TABLE 2). 32,33,45,48 When analyzed by intervention type, the most frequent result of shift length changes was no impact (8 of 20, 40%), 23,24,27,28,31,32,34,35 that of night float was an unfavorable impact (10 of 18, 56%), [35][36][37][38][39][41][42][43]46,47 and for protected time for sleep, 1 study reported a favorable outcome for resident wellness (1 of 2, 50%) 48 but no impact on patient care, while the other study was unfavorable for resident well-being (1 of 2, 50%). 49 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30,[33][34][35][36]41,43,46 A minority of studies found a favorable impact on resident well-being (4 of 17, 24%; TABLE 2). 32,33,45,48 When analyzed by intervention type, the most frequent result of shift length changes was no impact (8 of 20, 40%), 23,24,27,28,31,32,34,35 that of night float was an unfavorable impact (10 of 18, 56%), [35][36][37][38][39][41][42][43]46,47 and for protected time for sleep, 1 study reported a favorable outcome for resident wellness (1 of 2, 50%) 48 but no impact on patient care, while the other study was unfavorable for resident well-being (1 of 2, 50%). 49 …”
Section: Resultsmentioning
confidence: 99%
“…5 As a set, the studies had consistent shortcomings in 4 of the 6 dimensions of MERSQI quality measures. Most frequently, analyses were based on a single institution setting (19 of 27, 70%), [23][24][25]28,[31][32][33][34][35][36][37][38][39][40][41][42][43]45,49 outcomes were assessed through self-reporting (15 of 27, 56%), 27 …”
Section: Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…In a report on the implementation of a night float system at Children's Hospital in Boston, Chua and colleagues 4 found that total sleep time decreased under the night float system, and ultimately their program reverted back to a traditional call system. Similarly, Desai and colleagues 5 reported testing two systems-both compliant with the 2011 ACGME Common Program Requirements-on the inpatient internal medicine wards at Johns Hopkins.…”
Section: Problemmentioning
confidence: 99%
“…In addition, although night float systems decrease the amount of time that residents are in the hospital, such systems are associated with decreased sleep (Chua et al 2011). Therefore, residents working overnight in a night float system may be less well-rested and less able to engage in cognitively demanding work, including learning, than the same residents on day rotations (Durmer & Dinges 2005;Curcio et al 2006).…”
Section: Introductionmentioning
confidence: 99%